2003
DOI: 10.1038/nature01557
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative hydrogen adsorption on palladium requires aggregates of three or more vacancies

Abstract: During reaction, a catalyst surface usually interacts with a constantly fluctuating mix of reactants, products, 'spectators' that do not participate in the reaction, and species that either promote or inhibit the activity of the catalyst. How molecules adsorb and dissociate under such dynamic conditions is often poorly understood. For example, the dissociative adsorption of the diatomic molecule H2--a central step in many industrially important catalytic processes--is generally assumed to require at least two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
233
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(255 citation statements)
references
References 8 publications
(14 reference statements)
20
233
0
2
Order By: Relevance
“…The experimental measurements [1] at 65 K show that on the 3V ensembles the hydrogen sticking coefficient s is more than 50 times larger than on the 2V ones. The present model gives a reactivity of H-free trimers centered on top positions to be about 10 9 times higher than that of the 2V ensembles, and 10 6 times higher than that of the 3V H ones, and thus explains the experimental observations.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 1 Octobementioning
confidence: 99%
See 2 more Smart Citations
“…The experimental measurements [1] at 65 K show that on the 3V ensembles the hydrogen sticking coefficient s is more than 50 times larger than on the 2V ones. The present model gives a reactivity of H-free trimers centered on top positions to be about 10 9 times higher than that of the 2V ensembles, and 10 6 times higher than that of the 3V H ones, and thus explains the experimental observations.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 1 Octobementioning
confidence: 99%
“…In order to adsorb on such a surface the reactant molecules must find empty surface sites (active sites) created either by one missing adsorbate (vacancy) or by aggregates (ensembles) of vacancies. In the case of H 2 dissociation on Pd-a process of interest in many industrial reactions, including hydrogenation and fuel cell technologies -a recent scanning tunneling microscopy (STM) study [1] has revealed that the classically assumed mechanism where diatomic molecules require ensembles of two empty sites is too simplistic [1]. Indeed, Mitsui et al [1,2] have found that near saturation coverage the sites for the facile molecular dissociation on Pd(111) require ensembles of three or more H-free nearest neighbors fcc sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pd͑111͒ has been intensely investigated in the context of hydrogenation catalysis, electrolysis, and hydrogen purification. 20 This metal surface acts as a catalyst for the dissociation of H 2 molecules into H atoms 21,22 and is capable of storing hydrogen both on the surface [23][24][25] and in the subsurface region. 26,27 Thus, the affinity of the Pd͑111͒ surface towards hydrogen adsorption can be used as the regulator for the hydrogen transfer process between adsorbed building blocks and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the adsorption and absorption of hydrogen by Pd has been the subject of much experimental and theoretical work (6,(8)(9)(10)(11)(12)(13)(14). It is known that hydrogen can occupy subsurface sites that are stable absorption sites below the topmost surface layer of Pd atoms.…”
mentioning
confidence: 99%